Pengaruh Kemampuan, Budaya Organisasi, Komitmen Organisasi dan Kompensasi Terhadap Kinerja Pegawai Pada Kantor Bappeda Kabupaten Wajo - Suharjum; Agus Purwanto; Andi Sumangelipu (Yayasan Pengembangan Sumber Daya Insani Lamaddukelleng, 2025)
The purpose of this study is to analyze the influence of ability, organizational culture, organizational commitment and compensation on employee performance at the Wajo Regency Planning Agency office. This study was conducted at the Wajo Regency Regional Development Planning Agency (Bappeda) Office, with 99 employees as respondents using multiple regression methods with the help of SPSS version 26. The results of the study indicate that simultaneously or together the variables of ability, organizational culture, organizational commitment and compensation have a significant effect on the performance of Wajo Regency Bappeda employees, and partially the variables of ability, organizational culture, and compensation have a significant effect on employee performance. The results of this study also indicate that the compensation variable provides the greatest contribution to the performance of Wajo Regency Bappeda employees. The results of this study can be recommended that Bappeda management needs to improve employee ability, organizational culture, organizational commitment and better compensation management in the future. Improvement of ability through education, training, improving organizational culture and high organizational commitment and good performance from employees.